Tobacco and tobacco products use in adolescents after mpower policy: a systematic review - Yeşiltaş, Aysun (Journal of Dependence, 2020)
Tobacco control policy (MPOWER), was introduced in 2008, came into force in Turkey. In this study, it was aimed to systematically analyze the studies conducted between 2008-2019 on the use of tobacco and tobacco products in adolescents after the application. The study was conducted by searching the Google Scholar, National Thesis Center, and ULAKBİM databases according to the literature review criteria, and 17 articles were included in the study and examined. The tobacco product trial age was between 10-15 years old, and using tobacco products increased the use of other addictive substances. As the reasons for using tobacco products, the first place is the effect of friends, wannabe, curiosity, having fun and getting rid of boredom. As a result, it can be stated that MPOWER policies are generally effective, but they do not have a sufficient effect on tobacco products at the age of starting. It can be offered as a proposal to prepare the trainings on the use of tobacco products by taking adolescents to the center and to control the effects of the training.
Keywords: Tobacco; adolescents; systematic review